Assessment of Land Support as Direction of Land Development Central Pariaman District - Haryani, Haryani; Irianto, Agus; Syah, Nuhasan (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
ABSTRACT: Changes in the development of the built area of ​​Kota Pariaman can be seen in 1982 covering an area of ​​269.42 Ha, continuing to grow to 493.71 Ha in 2003. According to the developer, the growth of the built area in Kota Pariaman is influenced by economic factors (profit) and safety and comfort factors, namely considering safe areas from the tsunami disaster and free from flooding. While the community believes that the influencing factor is the proximity factor to public facilities and social facilities because of the completeness of the types of facilities many are located in the city center as well as the accessibility factor of the downtown area which has infrastructure conditions the good one. The problems in this study are; a) how is the carrying capacity of the North Pariaman District and b) how the direction of land development plan is in accordance with the carrying capacity of the land. The research objectives are a) analyzing land capability and b) formulating direction for land development plan in accordance with land capability in the District of North Pariaman. This type of research is descriptive research, GIS analysis methods and map overlays and analysis of land capability and land carrying capacity. Based on the physical condition of North Pariaman Subdistrict, Pariaman City, Land capability class 3 is a medium development capability class (C) and a maximum land cover ratio of 20%, the development direction is to limit the area built up and directed for non-settlement cultivation